Effectiveness of VR Technology in the Design of the Bali Megarupa V Virtual Exhibition - Sutanto, Shienny Megawati; Wardaya, Marina; Setia Budi, Hutomo; I Wayan, Adnyana (Institut Seni Indonesia Denpasar, 2024)
Virtual exhibitions offer a promising avenue for art appreciation in the digital age. However, limited research explores how these online spaces can foster emotional connections with art, a crucial aspect of the art experience. This study investigates the potential of immersive virtual reality (VR) to enhance engagement and emotional impact in virtual art exhibitions. Employing a multi-method approach combining literature review, user testing, and prototype development, the research identifies and evaluates design elements contributing to increased user engagement. This research employed a multi-method approach to understand how users engage with virtual art exhibitions. The study identified and evaluated the impact of specific design elements on user engagement by combining a literature review, user testing with a VR prototype, and subsequent analysis. The study focuses on critical elements like interactivity, personalization, storytelling, and multi-sensory experiences. User testing with 55 participants revealed the effectiveness of immersive design in fostering exploration, contemplation, and a sense of presence in the virtual space. This immersive design is the strategic integration of elements like interactivity, personalization, and storytelling within the VR environment. The research underscores the significance of immersive design, defined as the strategic integration of design elements to cultivate an emotional connection within a VR environment. This encompasses aspects like interactivity, personalization, and the incorporation of storytelling within the experience. Finally, the study offers practical recommendations for curators and designers to create virtual art experiences that resonate more deeply with audiences.